2014
DOI: 10.1186/s12888-014-0235-6
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and socio-demographic correlates of depressive symptoms among Cypriot university students: a cross-sectional descriptive co-relational study

Abstract: BackgroundPrevious findings in the literature suggest that the occurrence of depressive symptoms among university students is associated with specific socio-demographic characteristics. No related research studies have been conducted among university students in Cyprus. The current study aims to add more evidence to the literature by estimating the prevalence of clinical depressive symptoms and their association with individual, parental, academic and health-related behavior characteristics.MethodsA descriptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 54 publications
6
26
1
2
Order By: Relevance
“…Previous studies reported that married individuals were at higher risk of somatic symptoms compared to those who have not married on the basis of risk ratio (RR). 12,[16][17][18] The education, occupation, and income did not affect the somatic symptoms in this study. Previous studies showed that subjects with higher education level havehigher depression risk.…”
Section: Sociodemographic Factorscontrasting
confidence: 49%
“…Previous studies reported that married individuals were at higher risk of somatic symptoms compared to those who have not married on the basis of risk ratio (RR). 12,[16][17][18] The education, occupation, and income did not affect the somatic symptoms in this study. Previous studies showed that subjects with higher education level havehigher depression risk.…”
Section: Sociodemographic Factorscontrasting
confidence: 49%
“…Compared to other studies, it was lower than other neighbor countries; Thailand (47.01%) [33] and Brunei (43.36%) [34]; relatively comparable to Oman (27.70%) [35] and Cyprus (27.90%) [36]; higher than China (23.8%) [37], Ethiopia (21.60%) [38] and Syberia (23.60%) [19]. A study by Shamsuddin depression compared to the current study (29.4%) [8].…”
Section: Depression Related With Subjects Socio-demographic Factorsmentioning
confidence: 80%
“…Despite the fact that our findings regarding the rate of clinically relevant depressive symptoms were in line with those in the international literature, one has to underline their importance, since this is the first study, to our knowledge, that tackled this issue in Cyprus. Generally, there is limited data regarding the rate of depressive symptoms in the general population in Cyprus [ 45 ], as well as in adolescents; there is only one study conducted in young adults, in particular university students [ 46 , 47 ]. According to those research findings, the prevalence of clinically relevant depressive symptoms was 27.9%.…”
Section: Discussionmentioning
confidence: 99%